Do CVET agreements encourage employee participation in continuing vocational education and training? - Weis, Kathrin [Verfasser] (My University, 2025)
Company-based training is of significance in two regards. As well as serving as an important instrument enabling companies to cover their skill demand, it also makes a contribution towards ensuring staff employability. Participation in continuing vocational education and training (CVET) is, however, unevenly distributed. A role is also played by factors at the operational and institutional level. This article uses representative data from the BIBB Establishment Panel on Training and Competence Development (BIBB Training Panel) to investigate whether CVET agreements increase participation in such training by employees and whether this applies equally to all employee groups. (BIBB-Doku)
Keywords: S 1.5.3 Betriebliche Weiterbildung; S 2.1.6 Arbeits- & Tarifrecht; 370; Betriebliche Weiterbildung; Tarifvertrag; Betriebsvereinbarung; Weiterbildungsquote; Arbeitsanforderungen; BIBB-Qualifizierungspanel